Effect of 2 Types of Thoracholumbosacral Braces on Ankle and Knee Joint Co-contraction in Individuals with Kyphosis during Running - Milad Piran Hamlabadi; Amir Ali Jafarnezhadgero (مجله دانشگاه علوم پزشکی گرگان, 2023)
Milad Piran Hamlabadi , Amir Ali Jafarnezhadgero *